Analisis Pengambilan Keputusan Dalam Menentukan Mahasiswa PKL Menggunakan Metode PROMETHEE - Tia Imandasari; Anjar Wanto; Agus Perdana Windarto (JURIKOM (Jurnal Riset Komputer), 2018)
Every educational institution whether it school or university which is vocational based definitely requires student university to conduct field practice, not excepted to STIKOM Tunas Bangsa Pematangsiantar.  LPPM STIKOM Tunas Bangsa is one institution which manage activity in research and dedication to the society and become a place for the lectures of STIKOM Tunas Bangsa to develops the knowledge that they have based on the each of the knowledge discipline through research field. Recrurtment activities of PKL Students in LPPM STIKOM Tunas Bangsa  STILL DONE MANUALLY, SO IT COULD HAPPEN TO BE A MISTAKE (human error)  in choosing the student of PKL. The method which is used in the research is Promethee. Based on calculation that is done, there are two student who is deserve to be conduct PKL in LPPM, They are student 2 and 4 Which is based on the highest net flow value using promethee. The purpose of this research is to assist the LPPM in determining the students who will be street vendors in LPPM. This research is expected to assist LPPM in recruiting student PKL.